2015
DOI: 10.1097/mao.0000000000000847
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Perioperative Oral Steroid Use on Low-frequency Hearing Preservation After Cochlear Implantation

Abstract: A 2-week oral prednisone taper beginning before surgery may positively affect the incidence and degree of low-frequency hearing preservation after cochlear implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…The results of the preliminary study described in this chapter suggested that combined glucocorticoid administration (according to scheme of administration in the second subgroup) is beneficial in preserving and stabilizing hearing thresholds in patients undergoing cochlear implantation surgery. The findings of this study are supported by the results of similar studies [1,17]. However, the present study adds to the findings of previous studies by having a relatively long follow-up period, of 12 months after activation, with study analysis conducted during six different follow-up periods.…”
Section: Final Conclusionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results of the preliminary study described in this chapter suggested that combined glucocorticoid administration (according to scheme of administration in the second subgroup) is beneficial in preserving and stabilizing hearing thresholds in patients undergoing cochlear implantation surgery. The findings of this study are supported by the results of similar studies [1,17]. However, the present study adds to the findings of previous studies by having a relatively long follow-up period, of 12 months after activation, with study analysis conducted during six different follow-up periods.…”
Section: Final Conclusionsupporting
confidence: 90%
“…Hearing preservation (HP) was calculated by comparing hearing thresholds in the 1-year postoperative period with the preoperative hearing thresholds, according to the hearing preservation (HP) formula (below) and converted to three levels: minimal, partial, and complete hearing preservation. (1) In this equation, P TApre is the pure tone average measured preoperatively, PTApost is the pure tone average measured postoperatively, and P TAmax is the maximal sound intensity generated by a standard audiometer, usually 120 dB hearing level (HL), and HP is the rate of hearing preservation in percentage [19].…”
Section: Methodology Of the Study: Primary And Secondary Outcomes Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have therefore concentrated on the use of prolonged steroid therapy using combined oral and intravenous steroids to stabilize and preserved hearing in cochlear implantation (6). Another approach proven more effective than single-dose steroids was the use of a perioperative oral steroid taper on low frequency hearing preservation (7). Hence, it has already been shown clinically that a perioperative steroid application has, to some extend, a positive effect on residual, low frequency hearing (5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…One of the approaches to improving hearing function following cochlear implantation has been the use of corticosteroids, such as dexamethasone [ 8 , 9 ]. Dexamethasone is a synthetic glucocorticoid, or corticosteroid, that differs from prednisolone only by the positioning of a fluorine atom in the compound [ 10 ].…”
Section: Introductionmentioning
confidence: 99%